Sex-based metabolic and microbiota differences in roots and rhizosphere soils of dioecious papaya (Carica papaya L.) - Zhou, Yongmei; Pang, Ziqin; Yuan, Zhaonian; Fallah, Nyumah; Jia, Haifeng; Ming, Ray (Frontiers in Plant Science, 2022)
Dioecious plants have a high genetic variation that is important for environmental stress or human selection. A large number of studies have reported dimorphism morphism in morphology, physiology, as well as biotic and abiotic stress responses in dioecious plants. Here, we demonstrated the dimorphism of metabolic profile and the preference of some microorganisms in the roots and rhizosphere soil of male and female papaya. The metabolic composition of roots and rhizosphere soil were both significantly different between the males and females. For example, testosterone was up-regulated in male papaya roots and rhizosphere soil, whereas norgestrel was up-regulated in the female papaya roots, indicating a possible balance in papaya roots to control the sexual differentiation. Plant hormones such as BRs, JAs, SA and GAs were also detected among the differential metabolites in the roots and rhizosphere soil of dioecious papaya. In addition, some metabolites that have medicinal values, such as ecliptasaponin A, crocin, berberine and sapindoside A were also expressed differentially between the two sexes. Numerous differential metabolites from the papaya roots were secreted in the soil, resulting in the differences in microbial community structure in the roots and rhizosphere soil. Some nitrogen-fixing bacteria such as Allorhizobium-Neorhizobium-Pararhizobium-Rhizobium, Brevundimonas and Microvirga were enriched in the male papaya roots or rhizosphere soil. While Candidatus Solibacter and Tumebacillus, which utilize organic matters, were enriched in the roots or rhizosphere soil of the female papaya. Some differences in the fungi abundance were also observed in both male and female papaya roots.